Additional prognostic impact of the percentage of erythroid cells in the bone marrow of patients with myelodysplastic syndromes. (February 2019) - Neukirchen-Strapatsas, Judith; Tuechler, Heinz; Porta, Matteo Della; Fenaux, Pierre; Guerci, Agnès; Haas, Rainer; Rossi, Marianna; Sapena, Rosa; Sperr, Wolfgang R.; Strupp, Corinna; Stamatoullas, Aspasia; Valent, Peter; et al.
Highlights: Erythroid precursors show prognostic significance concerning OS and AML-free survival. Three risk categories according to the percentage of bmery can be defined. Bmery enhances the prognostic power of the IPSS-R for OS and AML-free survival. There is no correlation between bmery and peripheral blood counts. Abstract: In patients with myelodysplastic syndromes (MDS) the impact of the percentage of erythroid precursors in the bone marrow has been the subject of considerable debate, especially with regard to prognosis. We examined the prognostic impact of the percentage of erythroid cells in the bone marrow (bmery) in 2453 primary untreated MDS patients in a retrospective multi-center analysis. Bmery were quantified in bone marrow smears at the time of diagnosis and were correlated with overall survival (OS) and AML evolution. We identified three distinct risk categories: "< = 10% bmery" (poor), "11–25 or >45% bmery" (intermediate), and "26–45% bmery" (good) with distinct OS of 23, 40 and 48 months, respectively. The percentage of bmery showed prognostic significance concerning OS (Dxy = 0.08, p < 0.001) and AML-free survival (Dxy = 0.15, p < 0.001). Considering the IPSS-R by stratification, the Dxy were 0.09 for survival, and 0.18 for transformation (p < 0.001). Added to the IPSS-R, bmery enhances the prognostic power for both survival (Dxy = 0.39) and time to AML (Dxy = 0.59). Survival and time to AML differ in MDS according to the percentage of bmery. The best outcome was found in those who had normal or near normal bmery counts. Moreover, adding bmery as differentiating feature to the IPSS-R may enhance its prognostic significance.